Carteiras de mínima variância: comparação intertemporal com índices de mercado - Cavalcante, Daniel Menezes (2013)
In economies where low interest rates provide small profitability to conservative investments, such as fixed-income securities, investors must subject themselves to greater risk in search for higher yields. In such scenarios, these investors take interest in the stock market, where the increase in risk is rewarded by expectations of higher earnings, despite the risk level being higher than registered by fixed-income securities. However, the Modern Portfolio Theory shows that this risk can be reduced by diversification of assets. This research’s goal is to determine whether a quantitative model based on Modern Portfolio Theory is able to diversify a portfolio, reducing its risk to levels below those of the market portfolio, while providing higher yields than market benchmarks. The tests were based on historical data from 36 securities traded at BOVESPA between 1999 and 2012, and were conducted in sample windows of 12, 36, 60 and 120 observations. In shorter periods of analysis, the results were not conclusive, but as the investment horizon was expanded, the minimum variance portfolio outperformed investments based on applications in CDI and based on the Bovespa Index.